Application of the composite maps method for landslide susceptibility assessment and its potential use for other natural risk analyses - Sepúlveda, Sergio; Le Roux, Jacobus; Palma, Gisella (Investigaciones Geográficas: Una mirada desde el sur, 2013)
Composite maps have previously been applied to paleogeographic reconstructions and as an aid to mineral exploration. However, because they can combine different criteria that are used in risk and feasibility assessment into a single map with equal or weighted input from all the parameters, decisionmaking can be optimized. The methodology is particularly suitable for the evaluation of landslide hazard and susceptibility assessment, as it can combine the unfavourable factors typically associated with mountainous terrains. Composite maps also have the potential to standardize prediction and prevention criteria for different areas. The methodology is described together with an hypothetical example and a real case study in Patagonia, the results of which are compared with a susceptibility analysis of the same area using stochastic methods